2019
DOI: 10.1186/s40478-019-0857-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin light chain-1 serine-460 phosphorylation is altered in Alzheimer’s disease and regulates axonal transport and processing of the amyloid precursor protein

Abstract: Damage to axonal transport is an early pathogenic event in Alzheimer’s disease. The amyloid precursor protein (APP) is a key axonal transport cargo since disruption to APP transport promotes amyloidogenic processing of APP. Moreover, altered APP processing itself disrupts axonal transport. The mechanisms that regulate axonal transport of APP are therefore directly relevant to Alzheimer’s disease pathogenesis. APP is transported anterogradely through axons on kinesin-1 motors and one route for this transport in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 63 publications
3
37
1
Order By: Relevance
“…According to the recently proposed traffic jam theory [34], aging attenuates dynein dysfunction reproduces age-dependent endocytic disturbances, resulting in the intracellular accumulation of A␤PP and its ␤-cleavage products in neurons in cynomolgus monkeys. Another study reported that kinesin phosphorylation is involved in A␤PP processing [35]. In 4-month-old 3×Tg-AD mice, most of Vmes neurons possessed strong A␤ 42 -IR vesicles: however, we did not observe any abnormal behavior at this age, which suggests that the accumulation of A␤ 42 -IR granules in neurons itself is not a trigger for the progression of AD.…”
Section: Discussioncontrasting
confidence: 65%
“…According to the recently proposed traffic jam theory [34], aging attenuates dynein dysfunction reproduces age-dependent endocytic disturbances, resulting in the intracellular accumulation of A␤PP and its ␤-cleavage products in neurons in cynomolgus monkeys. Another study reported that kinesin phosphorylation is involved in A␤PP processing [35]. In 4-month-old 3×Tg-AD mice, most of Vmes neurons possessed strong A␤ 42 -IR vesicles: however, we did not observe any abnormal behavior at this age, which suggests that the accumulation of A␤ 42 -IR granules in neurons itself is not a trigger for the progression of AD.…”
Section: Discussioncontrasting
confidence: 65%
“…KIF5C levels were also reported to be reduced in familial, but not sporadic, AD [ 44 ]. Somewhat more consistent findings have been reported for changes in KLC1 in AD, with decreased protein levels [ 45 47 ] speculated to contribute to reduced anterograde axonal transport; nevertheless, others found no change in KLC1 [ 48 ]. In summary, existing observations with respect to AD are inconsistent, thus preventing a conclusion with respect to whether or not changes in KIF5 family members and KLC1 could contribute to changes in anterograde transport.…”
Section: Introductionsupporting
confidence: 69%
“…KLC1 is essential for anterograde transport of many cargoes and was reported to be downregulated in some, but not all, studies of AD [ 45 48 ]. To further explore possible shared molecular changes in AD and AD-DS, we measured KLC1 levels.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins associated with the mechanisms of AD pathology from nuclear factors associated with transcription, and exon processing, proteins associated with transport or secretion and signalling proteins associated with regulating cell survival and cell cycle as well as protein associated with the innate immune response and the cell-death, i.e. apoptotic, necrotic, necroptic and/or phagocytic, pathways were observed with Alzheimer's dementia [84].…”
Section: Discussionmentioning
confidence: 99%